Degradação ambiental e áreas suscetíveis à desertificação antrópica no município sergipano de Nossa Senhora da Glória - Silva, Max Cardoso (2016)
Humanity has evidenced significant changes in the enviromental causing impacts from different nature in the biosphera. Desertification for example, is a serious problem in places where it happens. In Brazil, the susceptible area to this process are located at the northeasthern, it is what we call "Sertão", where is the city of Sergipe "Nossa Senhora da Glória”. This study aimed to analyse the enviromental degradation and the process of anthropic desertification in the city of Nossa Senhora da Glória. Object of this study. So, to achieve this and other specific goals were used many methodological procedures associated to different stages, highlighting among them the bibliographic data and other documents that were useful to investigate the object of study, beside the outside activities. The results of this study show that in this city is evident in different places in the rural areas the prevalance of degraded areas and susceptible to the process of a thropic desertification, even if in reversible conditions with application of effective measures to combat the phenomenon. The human or the anthropic activities is was detected as being responsible as immediate causes the over cultivation, overgrazing, deforestation, and poor irrigation. Moreover, it must be... Recognized other deeper causes directly related to poverety, and it is not given other alternative to the farmers, instead of remove from the land as much as possible to solve their immediate needs, even compromising their long-term survival. On the other hand, the socio-economical vulnerability from the population of this region show low income, file expectancy, low economic productivity, concentration of land and wealth in the hands of a few, it is further agraveted by periodic droughts plaguing the semiarid region. It is conclused that thos whole situation reflected in the worsening of enviromental problems to be overcome depends on actions the go beyond sectoral polices and remedial guidance.